Influence of explant polarity on morphogenesis responses of Annona squamosa L. cultivated in vitro - Santana, José Raniere Ferreira de; Paiva, Renato; Oliveira, Lenaldo Muniz de; Lima-Brito, Alone; Pereira, Flávia Dionísio; Nepomuceno, Cristina Ferreira (SITIENTIBUS série Ciências Biológicas, 2009)
The influences of explant orientation on in vitro responses of Annona squamosa L. were evaluated. Hypocotyl and epicotyl segments were inoculated into test tubes with WPM medium supplemented with 8.87 µM BAP in the following orientations: horizontally on the medium surface, vertically upright retaining their natural polarity and vertically upright but inverted from their natural polarity (hypocotyl segments only). The test tubes were sealed with normal transparent plastic caps (either covered or not covered with PVC film) or with cotton plugs. After inoculation the tubes with the explants were maintained in a growth room under photosynthetically active radiation levels of 45-56 ìmol.m-2.s-1 and temperatures of 25 ± 3oC. The results showed that explant polarity affected organogenesis, and that the largest numbers of shoots (8.3 per explant) were found on hypocotyl explants placed vertically and retaining their natural polarity. No influences of the different test tube caps on morphogenetic responses of the explants were observed. The incubation of hypocotyl and epicotyl segments in a vertical position constitutes an efficient system for generating A. squamosa plants.